2017
DOI: 10.3390/polym9060202
|View full text |Cite
|
Sign up to set email alerts
|

Phenylboronic Acid-Functionalized Layer-by-Layer Assemblies for Biomedical Applications

Abstract: Recent progress in the development of phenylboronic acid (PBA)-functionalized layer-by-layer (LbL) assemblies and their biomedical applications was reviewed. Stimuli-sensitive LbL films and microcapsules that exhibit permeability changes or decompose in response to sugars and hydrogen peroxide (H 2 O 2 ) have been developed using PBA-bearing polymers. The responses of PBA-modified LbL assemblies arise from the competitive binding of sugars to PBA in the films or oxidative decomposition of PBA by H 2 O 2 . Elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 109 publications
0
25
0
Order By: Relevance
“…Furthermore, functional molecules can be easily immobilized in a film by modifying them with a polymer chain. For example, it has been reported that a multilayer thin film composed of a phenylboronic acid-modified polymer and polyvinyl alcohol decomposes in response to sugar and hydrogen peroxide [ 20 ]. The multilayer thin films composed of functional organic molecules, enzymes, and lectins also respond to substrates, such as pH [ 21 , 22 ], electrical potential [ 23 ], glucose, lactate, and hydrogen peroxide [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, functional molecules can be easily immobilized in a film by modifying them with a polymer chain. For example, it has been reported that a multilayer thin film composed of a phenylboronic acid-modified polymer and polyvinyl alcohol decomposes in response to sugar and hydrogen peroxide [ 20 ]. The multilayer thin films composed of functional organic molecules, enzymes, and lectins also respond to substrates, such as pH [ 21 , 22 ], electrical potential [ 23 ], glucose, lactate, and hydrogen peroxide [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results demonstrate the potential application of microparticles that undergo glucose-induced decomposition in the development of insulin delivery systems. In insulin delivery systems, insulin loading microparticles remain stable at normal levels of blood glucose (~5 mM), and glucose-induced delivery microparticles that release insulin only when the blood glucose is higher than the diabetic level (>10 mM) under physiological conditions are highly desirable [53]. Insulin release system depending on blood glucose will be realized by improving the suitable design of the film composition and the chemical structures of PBA-polymers.…”
Section: Discussionmentioning
confidence: 99%
“…PBA’s ability to form dynamic covalent bonds is expected to be applicable to many fields. In particular, the reaction between PBA and sugars has been widely investigated to develop blood glucose sensors [5,6,7,8,9,10,11,12] and glucose-responsive insulin delivery systems [13,14,15,16] for diabetes patients. However, the bond between PBA derivatives and glucose is not strong.…”
Section: Introductionmentioning
confidence: 99%